The Influence of Fluoxetine Therapy Combination of Rational Emotive Behaviour Therapy Againts the Improvement of Depression Symptoms, Cognition Function and Improvement of Brain-Derived Neurotrophic Factors Serum Levels in Patients with Depressive - Veraferial Muchtar; Erlyn Limoa; Nur Aeni M.A. Fattah; Andi Alfian Zainuddin; Ika Yustisia; Saidah Syamsuddin; Sonny Teddy Lisal (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Depression is a health problem in the world that has affected more than 300 million peoplearound the globe. This health problem is characterized by feeling sad, depressed, irritability as well asdistortion of cognition such as self-criticism, feeling of guilt, feeling of worthlessness, lower self-confidence,pessimism and hopelessness where their manifestations may vary for each individual. Method: In this study,it compares the fluoxetine group combination of Rational Emotive Behavior Therapy (REBT) with thefluoxetine group in the treatment of reducing symptoms of depression and improving cognitive function.This research is an experimental research with pre-test and post-test control group design. The samplingtechnique was done by using consecutive sampling for each group. Results: From the results of the studyit was found that the mean of Hamilton Depression Rating Scale (HDRS), the Indonesian version of theMontreal Cognitive Assessment (MoCA-Ina) and Brain-Derived Neurotrophic Factor (BDNF) serum levelsin the samples given by both groups experienced statistically improvements. Conclusion: there is an effecton the provision of fluoxetine therapy combination of REBT compared to fluoxetine therapy alone inimproving depressive symptoms, cognitive function as well as increasing BDNF serum levels.